Fostering Gender Equality in Higher education: Incorporating outcome-based measures into review manuals to enhance the quality assurance in Sri Lankan state universities - Shivany, S.; Dilogini, S.; Jegashini, K.; Thasika, T. (University of Ruhuna, Sri Lanka, 2024)
The field of higher education in Sri Lanka is undergoing significant changes to align with global standards and foster inclusive growth. However, a notable gap exists among universities in measuring gender equality and fostering inclusive growth through a quality assurance process. The purpose of this paper is to address the gap in measuring gender equality through quality assurance review manuals published by the University Grants Commission (UGC) for reviewing programmes and institutional performances. The goal is to emphasise the necessity of incorporating gender equality measures into academic evaluation frameworks and to propose strategies for implementing these measures to foster a more inclusive and equitable educational environment. A qualitative study utilised document analysis of manuals to uncover gaps in the quality assurance criteria for gender equality at state universities in Sri Lanka. To gain deeper insights, six focus group discussions were conducted with stakeholders, exploring their perspectives on gender measures in quality assurance. The manuals overlook crucial steps for promoting gender equality in higher education, such as equal facilities, gender-sensitive curriculum, increased women's participation, professional advancement, work-life balance, and antiharassment policies. Stakeholders emphasised the need for ten essential criteria as themes: policyimplementation, representation, access to resources, curriculum inclusivity, support services, grievance mechanisms, career progression, work-life balance, students' experience, and outcome-based measures.Integrating these ideas into institutional processes can foster a truly equitable academic community, improving the educational experience for all students and staff. Greater progress toward gender equality can be made by higher education institutions in Sri Lanka by addressing these gaps and putting the suggested standards into practice. In the end, this will improve academic performance while fostering a society that is more inclusive.
Keywords: Gender Equality; Higher Education; Outcome-Based Measures; Quality Assurance; Review Manuals